SOME QUESTIONS OF RURAL SETTLEMENTS DYNAMIC DISTRIBUTION IN REPUBLIC OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2011)
On the base of statistical data analysis the results and trends of migration dynamics of population and settlements distribution during the last 15 years are given. Special attention was paid to processes in Marzes during the last years.
Keywords: rural settlements; migration dynamics of population and settlements